2019
DOI: 10.1111/pcn.12854
|View full text |Cite
|
Sign up to set email alerts
|

Cortical surface architecture endophenotype and correlates of clinical diagnosis of autism spectrum disorder

Abstract: Aim Prior structural magnetic resonance imaging studies demonstrated atypical gray matter characteristics in siblings of individuals with autism spectrum disorder (ASD). However, they did not clarify which aspect of gray matter is related to the endophenotype (i.e., genetic vulnerability) of ASD. Further, because they did not enroll siblings of typically developing (TD) people, they may have underestimated the difference between individuals with ASD and their unaffected siblings. The current study aimed to add… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Such an increase of GI referred to the altered cortical folding and supported by previous studies, reporting increased local GI in the autistic brain 35 , 40 , 65 . FD, a measure of cortical complexity, statistically differed between ASD and TD groups of children in postcentral gyrus and banks of superior temporal sulcus in the left hemisphere and rostral middle frontal gyrus in the right hemisphere, which is also consistent with the previous studies, revealing atypical FD in ASD 10 , 38 . SD was the single surface-based parameter which did not significantly differed between groups of children in any ROIs which is contrary to Nordahl et al study 42 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such an increase of GI referred to the altered cortical folding and supported by previous studies, reporting increased local GI in the autistic brain 35 , 40 , 65 . FD, a measure of cortical complexity, statistically differed between ASD and TD groups of children in postcentral gyrus and banks of superior temporal sulcus in the left hemisphere and rostral middle frontal gyrus in the right hemisphere, which is also consistent with the previous studies, revealing atypical FD in ASD 10 , 38 . SD was the single surface-based parameter which did not significantly differed between groups of children in any ROIs which is contrary to Nordahl et al study 42 .…”
Section: Discussionsupporting
confidence: 90%
“…Other surface abnormalities, such as alterations in gyrification, sulcus depth, and fractal dimension/cortical (or folding) complexity, have also been observed in children with ASD 35 38 . Several studies, addressing Gyrification Index (GI), have shown the relationships between atypical GI in such language-related cortical regions as the temporal and inferior parietal cortices and the language abilities of children with ASD 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic abnormalities at the 15q11-q13 locus are fairly frequent in people with autism, and a "chromosome 15 phenotype" was described in individuals with chromosome 15 duplications. Among other candidate genes are the FOXP2, RAY1/ ST7, IMMP2L, and RELN genes at 7q22-q33 and the GABA(A) receptor subunit and UBE3A genes on chromosome 15q11-q13 [100].…”
Section: The Genetic Architecture Of Asdmentioning
confidence: 99%
“…Discovery of disease‐specific biomarkers or behavioral indicators with sufficient sensitivity is an important issue to improve the clinical diagnosis of mental illness. Magnetic resonance images, near‐infrared spectroscopy, genetic markers, cognitive functions, and eye movements are candidates . Of them, eye movement is representative of sensorimotor functions of the brain, and eye movement abnormalities have been reported in subjects with schizophrenia .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance images, near-infrared spectroscopy, genetic markers, cognitive functions, and eye movements are candidates. [1][2][3][4][5][6] Of them, eye movement is representative of sensorimotor functions of the brain, and eye movement abnormalities have been reported in subjects with schizophrenia. [7][8][9] It has been frequently reported that subjects with schizophrenia can be successfully distinguished from healthy individuals by using eye movements.…”
Section: Introductionmentioning
confidence: 99%